THEORETICAL BASIS OF STATISTICAL RESEARCH OF POPULATION EMPLOYMENT, IMPROVEMENT OF FINANCING IN BUSINESS ENTITIES - Shakirova Nigora Akhralovna (American Journals, 2023)
This article examines the challenges of unemployment and explores effective strategies to ensure a well-employed population in business entities. By focusing on key areas such as education, entrepreneurship, and government initiatives, this article aims to provide insights into fostering a robust job market and promoting economic growth.
Keywords: Employment, Business Entities, Workforce, Job Market, Prospects, Strategies.